Surgical management of urethral diverticula in women: a systematic review. Issue 7 (July 2016) - Bodner-Adler, Barbara; Halpern, Ksenia; Hanzal, Engelbert
Abstract Urethral diverticula (UD) are pouch-like outgrowths of the urethral lumen and surgery is by far the most common approach in symptomatic patients. The aim of this systematic review was to evaluate surgical techniques and outcomes in adult women with urethral diverticula. Our secondary objective was to determine the types of study designs. A systematic review of the literature was conducted. Medline, Cinahl and Embase were used as data sources. One hundred and eight studies, including 1, 947 patients, remained for final analysis. We summarised 40 single case reports and 68 case series. Overall, transvaginal resection of the UD ± reconstruction was performed in the majority of patients (84 %), followed by marsupialisation (3.8 %) and transurethral endoscopic unroofing (2.0 %). Various other surgical techniques were reported in 181 out of 1, 858 cases (9.7 %). Nineteen studies, dealing with 584 patients in all, evaluated a combination of vaginal diverticulectomy with an additional surgical procedure. Fifty-six out of 108 studies (52 %) documented the resolution of symptoms, describing 717 out of 1, 044 patients in all being completely symptom-free after surgery. Only 50 out of 108 studies (46.2 %) provided detailed information on the length of follow-up, but showed a poor reporting standard regarding prognosis. Complications were studied only selectively. Because of the inconsistency of these data, it was impossible to analyse them collectively. There were no comparative studies on the different types of surgery in women with urethral diverticula. Overall, the non-comparative nature of the current evidence on the surgical management of UD does not allow any accurate estimation of success and complication rates.